Intravenous acetaminophen in a faith-based hospital in Nigeria: A randomized trial of a labor analgesic. (2024)
Background: The undesirable maternal and neonatal side effects of opioid analgesics, and less ready availability and affordability of epidural analgesia in resource poor settings has necessitated the search for a safe, efficacious, affordable and readily available labor analgesic. Aim: To determine the efficacy, safety and acceptability of intravenous acetaminophen as an intra partum analgesic. Methods: A randomized controlled double-blinded study involving 162 consenting pregnant women in labor, assigned to two groups, each receiving either 900mg of intravenous acetaminophen or an equal volume of normal saline. The Numeric Rating Scale and Likert scale were used to measure the degree of pain experienced and the level of acceptability. Data was analyzed using IBM SPSS Statistics for Windows, version 24.0. The student’s T-test, Chi-square test (χ2), Hazard ratio and Mann-Whitney U test were used to test associations with level of statistical significance set at p < 0.05. Results: At 15, 60-, 120-, 180- and 240-minutes post-administration of medications, there was a statistically observed significant difference between the pain scores of women in the two groups (t = 3.71, 7.58, 9.45, 9.48, and 9.18 respectively, p < 0.001). The participants in the acetaminophen group had better pain relief than those in the placebo group (Hazard ratio = 0.51; 95% CI: 0.35 – 0.73; p < 0.001). There was no significant difference between the two groups in terms of side effects of administered agents. The difference between the maternal level of acceptability of acetaminophen and placebo as labor analgesia was found to be statistically significant (χ2 = 72.981, p < 0.001). Conclusions: In poor resource settings, intravenous acetaminophen is an effective alternative labor analgesic agent with no adverse maternal and neonatal side effects.